Genome-wide location analysis reveals a role of TFIIS in RNA polymerase III transcription - Ghavi-Helm, Yad (Cold Spring Harbor Laboratory Press, 2008)
TFIIS is a transcription elongation factor that stimulates transcript cleavage activity of arrested RNA polymerase II (Pol II). Recent studies revealed that TFIIS has also a role in Pol II transcription initiation. To improve our understanding of TFIIS function in vivo, we performed genome-wide location analysis of this factor. Under normal growth conditions, TFIIS was detected on Pol II-transcribed genes, and TFIIS occupancy was well correlated with that of Pol II, indicating that TFIIS recruitment is not restricted to NTP-depleted cells. Unexpectedly, TFIIS was also detected on almost all Pol III-transcribed genes. TFIIS and Pol III occupancies correlated well genome-wide on this novel class of targets. In vivo, some dst1 mutants were partly defective in tRNA synthesis and showed a reduced Pol III occupancy at the restrictive temperature. In vitro transcription assays suggested that TFIIS may affect Pol III start site selection. These data provide strong in vivo and in vitro evidence in favor of a role of TFIIS as a general Pol III transcription factor.